"You would expect the successful person to be the man". Issue 3 (14th September 2015) - Silke Tegtmeier, Prof. Jay Mitra, Dr.; Jones, Sally
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to to explore power and legitimacy in the entrepreneurship education classroom by using Pierre Bourdieu's sociological and educational theories. It highlights the pedagogic authority invested in educators and how this may be influenced by their assumptions about the nature of entrepreneurship. It questions the role of educators as disinterested experts, exploring how power and gendered legitimacy "play out" in staff–student relationships and female students' responses to this. Design/methodology/approach – A multiple-method, qualitative case study approach is taken, concentrating on a depth of focus in one UK's higher education institution (HEI) and on the experiences, attitudes and classroom practices of staff and students in that institution. The interviews, with an educator and two students, represent a self-contained story within the more complex story of the case study. Findings – The interviewees' conceptualization of entrepreneurship is underpinned by acceptance of gendered norms, and both students and staff misrecognize the masculinization of entrepreneurship discourses that they encounter as natural and unquestionable. This increases our understanding of symbolic violence as a theoretical construct that can have real-world consequences. Originality/value – The paper makes a number of theoretical and empirical contributions. It addresses an important gap in the literature, as educators and the impact of their attitudes and perceptions on teaching and learning are rarely subjects of inquiry. It also addresses gaps and silences in understandings of the gendered implications of HE entrepreneurship education more generally and how students respond to the institutional arbitration of wider cultural norms surrounding entrepreneurship. In doing so, it challenges assertions that Bourdieu's theories are too abstract to have any empirical value, by bridging the gap between symbolic violence as a theory and its manifestation in teaching and learning practices.